UhAVR1, an HR-Triggering Avirulence Effector of Ustilago hordei, Is Secreted via the ER–Golgi Pathway, Localizes to the Cytosol of Barley Cells during in Planta-Expression, and Contributes to Virulence Early in Infection - Ana Priscilla Montenegro Alonso; Shawkat Ali; Xiao Song; Rob Linning; Guus Bakkeren (Journal of Fungi, 2020)
The basidiomycete Ustilago hordei causes covered smut disease of barley and oats. Virulence effectors promoting infection and supporting pathogen lifestyle have been described for this fungus. Genetically, six avirulence genes are known and one codes for UhAVR1, the only proven avirulence effector identified in smuts to date that triggers complete immunity in barley cultivars carrying resistance gene Ruh1. A prerequisite for resistance breeding is understanding the host targets and molecular function of UhAVR1. Analysis of this effector upon natural infection of barley coleoptiles using teliospores showed that UhAVR1 is expressed during the early stages of fungal infection where it leads to HR triggering in resistant cultivars or performs its virulence function in susceptible cultivars. Fungal secretion of UhAVR1 is directed by its signal peptide and occurs via the BrefeldinA-sensitive ER–Golgi pathway in cell culture away from its host. Transient in planta expression of UhAVR1 in barley and a nonhost, Nicotiana benthamiana, supports a cytosolic localization. Delivery of UhAVR1 via foxtail mosaic virus or Pseudomonas species in both barley and N. benthamiana reveals a role in suppressing components common to both plant systems of Effector- and Pattern-Triggered Immunity, including necrosis triggered by Agrobacterium-delivered cell death inducers.